Prevalence of Hymenolepis spp. in House Mice in Baghdad City, Iraq - Majeed, Shaymaa A; Al-Amery, Amer M (The Iraqi Journal of Veterinary Medicine, 2021)
The prevalence of house mice (Mus musculus) Hymenolepiasis was determined in Baghdad, Iraq to study the effects of location, sex, and months on the infection rate of Hymenolepis spp. in house mice. Fifty house mice were captured from Abu Ghraib and Al-Ameriya, Baghdad, Iraq and examined for detecting parasites in laboratory in College of Veterinary Medicine, University of Baghdad. The total infection prevalence of intestinal parasites was 11 (22%) out of 50 samples, the higher prevalence was 28.57% and found in Abu Ghraib area, while lower was (13.63%) and recorded in Al-Ameriya area. The study revealed that the house mice were infected with two species of Hymenolepis: Hymenolepis nana 4 (8%) and Hymenolepis diminuta 7(14%). The intestinal parasites revealed a significance prevalence value (P<0.05). There was statistical difference in between males and females in parasites infection, in which the higher rate was 8 (27.58%) and recorded in males and the lower was 3 (14.28%) and observed in females. The monthly distribution of confirmed cases over a 9-month period revealed that reported cases of house mice and Hymenolepiasis increased significantly (P<0.01) in autumn (65.44%), followed by winter (15.38%), and summer (13.33%). The findings showed that house mice play an important role in the spread of zoonotic parasitic illnesses to people, as well as attention must pay to public health.